Manipulating multicrystalline grain size in CH3NH3PbI3 thin films for application in photovoltaics. (1st December 2016) - Chen, Cheng-Chiang; Chang, Sheng Hsiung; Chen, Lung-Chien; Cheng, Hsin-Ming; Tseng, Zong-Liang; Wu, Chun-Guey
Highlights: High-quality CH3 NH3 PbI3 thin films were fabricated using a one-step spin-coating method. The CH3 NH3 PbI3 thin film is a multicrystalline material. The grain size in CH3 NH3 PbI3 thin films was increased from 230 nm to 1340 nm. The VOC (average PCE) was improved from 0.85 V (13.02%) to 0.9 V (13.66%). Abstract: The multicrystalline grain size of CH3 NH3 PbI3 thin films can be manipulated by using different precursor concentrations which dominate the competition between the nucleation and crystal growth during the one-step spin-coating process with the toluene washing treatment. A comprehensive study was carried out to explore the correlation between the structural properties and the exciton dynamics in CH3 NH3 PbI3 thin films fabricated using various precursor concentrations from 1.25 M to 1.65 M. The experimental results show that the precursor concentration influences the grain size and exciton dynamics of the resultant CH3 NH3 PbI3 thin films which were fabricated on top of poly(3, 4-ethylenedioxythiophene)-polystyrene sulfonate/ITO/glass substrates. The higher average power conversion efficiency (PCE) of 13.66% achieved can be explained as being due to the formation of a larger CH3 NH3 PbI3 grain size which thus results in higher photocurrent generation and lower voltage loss. It is predicted that the PCE can be further improved when the voltage loss across the CH3 NH3 PbI3 thin film is minimized.